Fish Fauna in the Ogan River, South Pemulutan District, Ogan Ilir - Elva Dwi Harmilia; Khusnul Khotimah; Irkhamiawan Ma'ruf (Journal of Global Sustainable Agriculture, 2024)
Research on the diversity of fish fauna has been widely carried out, especially in Indonesia, even in some areas has decreased, especially in rivers due to many factors. The Ogan River that flows through Ogan Ilir Regency is a multipurpose river for the community, not only for daily needs, transportation, aquaculture activities, and capture fisheries. Currently, information on fish fauna in the Ogan River in Ogan Ilir Regency has not been verified and has not been published in detail. The study aims to determine the types of fish caught, diversity index, uniformity index, abundance index, and dominance index. The research was conducted in the Ogan River, South Pemulutan Subdistrict, Ogan Ilir Regency with a survey method that determines the station point by purposive sampling and produces three stations with different characteristics. Sampling of fish was done 8 times for three months using a gill net. The results showed that in the Ogan River 24 species of fish were found with a total catch of 276 fish classified into 14 families, namely dukang fish, dukang yellow fish, long whiskers catfish, asian redtail catfish, marble goby, milkfish, duskyfin glassy perchlet, striped snakehead, nile tilapia, long tongue sole, silver barb, tinfoil barb, beardless barb, black sharkminnow, bonylip barb, umbut fish, sleepy goby, kissing gourami, amazon sailfin catfish, giant prawn, giant gourami, pangasius juaro, malayan leaffish, and lais fish. All stations show a moderate diversity index value of 1.72-2.842, the uniformity index value shows evenly distributed at all stations, namely 0.898 - 1.816, the abundance index value is 1 which indicates less abundant at all stations and the dominance index shows a low value that ranges from 0.068-0.094 or no dominating species.